2000
DOI: 10.1177/096368970000900205
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Survival of Grafted Dopaminergic Neurons: A Review over Current Approaches

Abstract: Neural transplantation is developing into a therapeutic alternative in Parkinson's disease. A major limiting factor is that only 3-20% of grafted dopamine neurons survive the procedure. Recent advances regarding how and when the neurons die indicate that events preceding actual tissue implantation and during the first week thereafter are crucial, and that apoptosis plays a pivotal role. Triggers that may initiate neuronal death in grafts include donor tissue hypoxia and hypoglycemia, mechanical trauma, free ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
188
2
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(206 citation statements)
references
References 141 publications
(54 reference statements)
14
188
2
2
Order By: Relevance
“…This low survival of dopamine neurons following transplantasites for graft placement, and the ability to restore full and homogenous dopaminergic innervation throughout tion means that for sufficient functional benefits to be achieved in Parkinson's disease patients, transplantation the striatum. One possible reason for the poor survival of dopaof mesencephalic tissue from four to eight human embryos is required per side of the brain (11). The requiremine neurons may be because of oxidative stress caused by free radicals, a mechanism that has been implicated ment for large quantities of human embryonic tissue for each patient makes widespread clinical delivery impracin the death of substantia nigra dopamine neurons in Parkinson's disease (16,29,33).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This low survival of dopamine neurons following transplantasites for graft placement, and the ability to restore full and homogenous dopaminergic innervation throughout tion means that for sufficient functional benefits to be achieved in Parkinson's disease patients, transplantation the striatum. One possible reason for the poor survival of dopaof mesencephalic tissue from four to eight human embryos is required per side of the brain (11). The requiremine neurons may be because of oxidative stress caused by free radicals, a mechanism that has been implicated ment for large quantities of human embryonic tissue for each patient makes widespread clinical delivery impracin the death of substantia nigra dopamine neurons in Parkinson's disease (16,29,33).…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that oxidatical; therefore, increasing dopamine graft survival needs 764 BAGGA, DUNNETT, AND FRICKER-GATES tive stress caused by cellular trauma during dissection survival both in vitro and in grafts transplanted into the unilateral 6-OHDA-lesioned rat brain. Ascorbic acid and tissue preparation is one of the mechanisms contributing to poor neuronal survival, potentially by inducing was the only antioxidant used because previous reports have shown that the majority of dopamine cell death apoptosis in transplanted neurons (11,39). Removing cells from low oxygen environments and exposing them occurs over the first 24 h from cell dissociation, and this coincides with rapid ascorbic acid depletion in cultured to atmospheric oxygen levels of 20% during the dissection procedure may also promote oxidative stress and cells (23).…”
Section: Introductionmentioning
confidence: 99%
“…The death of the majority (~90-95%) of transplanted DA neurons from the fetal ventral mesencephalon (VM) soon after grafting in rat (Brundin et al, 2000) and human (Olanow et al, 1996) can serve to limit the success of the neural transplantation treatment strategy for Parkinson's disease. An important contributor to this poor survival appears to be the environment of the adult host brain, which may be less than optimal for the survival and growth of grafted immature neurons.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to study transplantation of fetal instead of neonatal neuroretina to see if the greater plasticity of such tissue would enhance graft-host integration. Another rationale for using fetal donor tissue is that in contrast to neonatal tissue, it is available after ethical approval and has been used for clinical transplantation trials in RP patients as well as in patients suffering from Parkinson's disease [3,6]. To further promote graft-host integration, we used host eyes more severely affected by the disease, i.e with a retina in which very few of the rod photoreceptors remain, corresponding to an RP patient with a significant reduction in vision.…”
Section: Introductionmentioning
confidence: 99%